Relationship Between Knowledge Level of Chronic Kidney Failure Patients and Hemodialysis Therapy Compliance at Gunung Jati Cirebon Regional Hospital - Novia, Kokom; Ulfah, Siti Maria; Suhaeni, Eni (Syntax Corporation, 2025)
Chronic Kidney Disease (CKD) is a condition due to a progressive and irreversible decline in kidney function. The incidence of Chronic Kidney Failure worldwide reaches 10% of the population. This study aims to determine the relationship between the level of knowledge of Chronic Kidney Failure patients and adherence to Hemodialysis therapy at Gunung Jati Regional Hospital, Cirebon. This study used observational analytic with a cross-sectional design carried out at Gunung Jati Regional Hospital in June-July 2024. Data collection used questionnaires and medical records. The sample used in this study was 139 people using probability sampling techniques. The analysis test was carried out using spearmen. There were 34 respondents (58.6%) who had sufficient knowledge, 18 respondents (31.5%) were good, and 6 respondents (10.3%) were said to be poor. The majority of respondents had a compliance level of 50 (86.2%), and 8 respondents (13.8%) were non-compliant. The results of the Spearman correlation test showed that there was a significant relationship (p = 0.034) between the level of knowledge of chronic kidney failure patients and adherence to hemodialysis therapy at the Gunung Jati Regional Hospital in Cirebon and a value (r = 0.280) with a weak correlation strength. There is a relationship between the level of knowledge of chronic kidney failure patients and adherence to hemodialysis therapy at the Gunung Jati Regional Hospital in Cirebon.